Edukacja medialna w kontekście cyberpsychologii: nowe perspektywy badania mediów i ich użytkowników we współczesnej cywilizacji medialnej - OGONOWSKA, AGNIESZKA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Agnieszka Ogonowska, Edukacja medialna w kontekście cyberpsychologii: nowe perspektywy badania mediów i ich użytkowników we współczesnej cywilizacji medialnej [Media education in the context of cyber-psychology: new perspectives for media and user research in contemporary media civilisation]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 93-109. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.05 The aim of the article is to show new perspectives of research and development of media, digital and information competences in the context of knowledge and research in (cyber) psychology. It draws attention to the functions of media education in relation to civil society, the society of knowledge, and the society of communication democracy. In the modern media civilization, these competences, acquired through formal and informal education, are the basis for conscious functioning in many social roles (eg citizen, consumer) and dealing with disinformation. The last part of the article is dedicated to shaping media competences in young children (2.5-7 years old), who should develop these skills under the care of an adult. The task of educational environments is the systematic implementation of home media education that facilitates the child's functioning in the environment of traditional and new media.